Nonperturbative electron-ion-scattering theory incorporating the Møller interaction - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2012)
Relativistic distorted-wave studies by Fontes et al. [Phys. Rev. A 47, 1009 (1993)] demonstrated that the generalized Breit interaction (equivalently, the Møller interaction) can affect electron-impact excitation cross sections of hydrogen like U91+ by more that 50% in comparison to calculations that employ the Coulomb interaction alone. We present calculations that investigate the effects of both the Møller interaction and close coupling in the calculation of electron-impact excitation cross sections. Electron scattering from U91+ is used as a test case. The relativistic convergent close-coupling (RCCC) method is nonperturbative and we emphasize the restrictions and subsequent limitations associated with employing the Møller interaction in the RCCC method.